In global change research, where modelling of CO2 fluxes from plants is an important component in determining vegetation capacity to protect the climate, mechanistic-based modelling is needed when projection of future CO2 absorption dynamics need to be estimated more accurately. Rubisco is the world’s most abundant protein in plants and has the job of uniquely preparing CO2 for chemical reduction. Rubisco activity in the leaf, described by Vcmax, can be estimated from gas exchange measurements - TANIA JUNE (HAYATI Journal of Biosciences, 2011)
In global change research, where modelling of CO2 fluxes from plants is an important component in determining vegetation capacity to protect the climate, mechanistic-based modelling is needed when projection of future CO2 absorption dynamics need to be estimated more accurately. Rubisco is the world’s most abundant protein in plants and has the job of uniquely preparing CO2 for chemical reduction. Rubisco activity in the leaf,  described by Vcmax, can be estimated from gas exchange measurements of the initial slope of the response of CO2 assimilation rate, A, to intercellular [CO2]. This technique of estimation is favourable because it can avoid the uncertainties and difficulties when Vcmax is obtained directly by extraction and biochemical assay in artificial media. Rate of assimilation of soybean plants grown at different temperature (20/15, 25/20, and 32/27 oC day/night temperature) and [CO2] (350 and 700 mmol mol-1), were measured using gas exchange. The effect of wall conductance (gw) on the parameterization of assimilations rate was observed. The temperature dependence of Vcmax depends strongly on wall conductance, where the shape of the curve would change significantly if finite wall conductance were included in the analysis. The implication is that it changes the values and interpretation of the temperature response of assimilation rate